Mechanical force increases tooth movement and promotes remodeling of alveolar bone defects augmented with bovine bone mineral - Jie Deng; Zi-Meng Zhuang; Xiao Xu; Bing Han; Guang-Ying Song; Tian-Min Xu (SpringerOpen, 2024)
Abstract Background Orthodontic tooth movement (OTM) in a region containing alveolar bone defects with insufficient height and width is hard to achieve. Bovine bone mineral (Bio-Oss) is available to restore the alveolar defect; however, whether the region augmented with a bovine bone mineral graft (BG) is feasible for OTM, and the mechanisms by which macrophages remodel the BG material, is uncertain under the mechanical force induced by OTM. Material and methods Rats were divided into three groups: OTM (O), OTM + BG material (O + B), and Control (C). First molars were extracted to create bone defects in the O and O + B groups with bovine bone mineral grafting in the latter. Second molars received OTM towards the bone defects in both groups. After 28 days, maxillae were analyzed using microfocus-computed tomography (μCT) and scanning-electron-microscopy (SEM); and macrophages (M1/M2) were stained using immunofluorescence. THP-1 cell-induced macrophages were cultured under mechanical force (F), BG material (B), or both (F + B). Phagocytosis-related signaling molecules (cAMP/PKA/RAC1) were analyzed, and conditioned media was analyzed for MMP-9 and cytokines (IL-1β, IL-4). Results Our study demonstrated that alveolar defects grafted with BG materials are feasible for OTM, with significantly increased OTM distance, bone volume, and trabecular thickness in this region. SEM observation revealed that the grafts served as a scaffold for cells to migrate and remodel the BG materials in the defect during OTM. Moreover, the population of M2 macrophages increased markedly both in vivo and in cell culture, with enhanced phagocytosis via the cAMP/PKA/RAC1 pathway in response to mechanical force in combination with BG particles. By contrast, M1 macrophage populations were decreased under the same circumstances. In addition, M2 macrophage polarization was also indicated by elevated IL-4 levels, reduced IL-1β levels, and less active MMP-9 in cell culture. Conclusion This study explored the mechanisms of mechanical force-induced alveolar bone remodeling with bovine bone mineral grafts during OTM. The results might provide molecular insights into the related clinical problems of whether we can move teeth into the grafted materials; and how these materials become biologically remodeled and degraded under mechanical force.